2022
DOI: 10.1063/5.0076269
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the high-efficiency and low-damage abrasive processing mechanism for SiC based on the SPH simulation of single-grain indentation and scratching

Abstract: During the wafer fabrication procedure, abrasive machining occupies a large proportion in time and economic cost, mainly including grinding, lapping, and polishing. The third-generation semiconductor materials, represented by SiC, have the properties of high hardness, large brittleness, and strong chemical inertness, which make abrasive machining more challenging. To improve the machining efficiency and quality, this paper applied the smoothed particle hydrodynamics (SPH) method to simulate the machining behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In this study, the transient structural analysis was used as an alternative to the explicit dynamics method for simulating the scratch test to save time and minimize expenses. However, recent research has been actively exploring the application of a method using Smooth-Particle Hydrodynamics (SPH) coupled with the Finite Element Method (FEM) for grinding [28][29][30][31]. This method offers the advantages of time efficiency for slow behavior and the ability to simulate realistic behavior.…”
Section: Finite Element Analysis (Fea)mentioning
confidence: 99%
“…In this study, the transient structural analysis was used as an alternative to the explicit dynamics method for simulating the scratch test to save time and minimize expenses. However, recent research has been actively exploring the application of a method using Smooth-Particle Hydrodynamics (SPH) coupled with the Finite Element Method (FEM) for grinding [28][29][30][31]. This method offers the advantages of time efficiency for slow behavior and the ability to simulate realistic behavior.…”
Section: Finite Element Analysis (Fea)mentioning
confidence: 99%
“…Two scratching experiments are conducted under three different conditions to verify the validity of the simulation method. Shi et al [19] adopted the SPH method to simulate the single abrasive scratching of SiC wafers to investigate the micromechanical mechanisms affecting the parameters during SiC grinding processing, and the results showed that higher velocity can reduce the subsurface damage and surface roughness. Higher scratch depths caused larger surface defects and damage.…”
Section: Introductionmentioning
confidence: 99%